Perceptions of health professionals about the quality of communication and deliberation with the patient and its impact on the health decision making process - Eduardo Osuna; Antonio Pérez-Carrión; María D. Pérez-Cárceles; Francisco Machado (SAGE Publishing, 2018)
The information process is considered a core element in decision-making and an obligatory matter of concern for the health professional. Rather than information per se, we should perhaps mention the need for communication between the health professional and the patient, which should be appropriate to each specific case and situation. Interaction and communication during the relationship generates a degree of trust that contributes to improving care quality and health-related results. The aim of this study is to know the perception of professionals on the quality of communication and its impact on the decision-making process of the patient and the degree of involvement of health professionals in the process of communication with the patient. A sample of 2186 health professionals (1578 nurses, 586 physicians, and 22 pharmacists) was studied. A questionnaire composed of 20 items dealing with the process of communication with the patient and obtaining informed consent was administered. Our study revealed the high consideration that professionals hold of their communication skills with patients since almost 80% of those surveyed, think they are sufficiently skilled in this area. Professionals refers that nurses are most skilled at communicating with patients. Communication in the clinical relationship must not only serve as a way for the professional to obtain information from the patient on their pathology, but also as a means to inform patients so that they understand their illness. Patients also like to feel that they are being listened to and are co-participants in the care process. Communication should be a continuous object of study for all health professionals, both in primary and specialised attention.